Polytypism in few-layer gallium selenide - Lim, Soo Yeon; Lee, Jae Ung; Kim, Jung Hwa; Liang, Liangbo; Kong, Xiangru; Nguyen, Thi Thanh Huong; Lee, Zonghoon; Cho, Sunglae; Cheong, Hyeonsik (Nanoscale, 2020)
Gallium selenide (GaSe) is one of the layered group-III metal monochalcogenides, which has an indirect bandgap in the monolayer and a direct bandgap in bulk unlike other conventional transition metal dichalcogenides (TMDs) such as MoX2 and WX2 (X = S and Se). Four polytypes of bulk GaSe, designated as β-, ϵ-, γ-, and δ-GaSe, have been reported. Since different polytypes result in different optical and electrical properties even with the same thickness, identifying the polytype is essential in utilizing this material for various optoelectronic applications. We performed polarized Raman measurements on GaSe and found different ultra-low-frequency Raman spectra of inter-layer vibrational modes even with the same thickness due to different stacking sequences of the polytypes. By comparing the ultra-low-frequency Raman spectra with the theoretical calculations and high-resolution electron microscopy measurements, we established the correlation between the ultra-low-frequency Raman spectra and the stacking sequences of trilayer GaSe. We further found that the AB-type stacking is more stable than the AA′-type stacking in GaSe.
Keywords: Conventional transitions; Gallium selenides; Optical and electrical properties; Optoelectronic applications; Stacking sequence; Theoretical calculations; Ultra low frequencies; Vibrational modes